Effective Ways in Teaching English as Foreign Languageto Young Learners with Various Learning Styles - Fahriany Fahriany; Fahri Haswani (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2017)
In response to learning revolution, teaching is not only transferring knowledge to students but also it should be conducted by acommodating students’ learning styles.By viewing to these two factors, the teaching learning process will be more successful. This study presents the strategies to improve students’ speaking skill related to age and learning styles. The teaching strategies were developed by analysing the students’ needs, students’ wants, and students’ lack.